A comparison of characteristics and outcomes of patients with community-acquired and hospital-acquired COVID-19 in the United Kingdom: An observational study. (March 2021) - Shiwani, Haaris A.; Bilal, Muhammad; Shahzad, Muhammad U.; Rodrigues, Alson; Suliman, Jehad A.; Soban, Muhammad; Mirza, Shahzeb; Lotca, Nicoleta; Ruslan, Mohammed R.; Memon, Danyal; Arshad, Muhammad A.; Fatima, Kiran; et al.
Abstract: Background and objectives: Reports comparing the characteristics of patients and their clinical outcomes between community-acquired (CA) and hospital-acquired (HA) COVID-19 have not yet been reported in the literature. We aimed to characterise and compare clinical, biochemical and haematological features, in addition to clinical outcomes, between these patients. Methods: This multi-centre, retrospective, observational study enrolled 488 SARS-CoV-2 positive patients - 339 with CA infection and 149 with HA infection. All patients were admitted to a hospital within the University Hospitals of Morecambe Bay NHS Foundation Trust between March 7th and May 18th, 2020. Results: The CA cohort comprised of a significantly younger population, median age 75 years, versus 80 years in the HA cohort (P = 0· 0002). Significantly less patients in the HA group experienced fever (P = 0· 03) and breathlessness (P < 0· 0001). Furthermore, significantly more patients had anaemia and hypoalbuminaemia in the HA group, compared to the CA group (P < 0· 0001 for both). Hypertension and a lower median BMI were also significantly more pronounced in the HA cohort (P = 0· 03 and P = 0· 0001, respectively). The mortality rate was not significantly different between the two cohorts (34% in the CA group and 32% in the HA group, P = 0· 64). However, the CA group required significantly greater ICU care (10% versus 3% in the HA group, P = 0· 009). Conclusion: Hospital-acquired and community-acquired COVID-19 display similar rates of mortality despite significant differences in baseline characteristics of the respective patient populations. Delineation of community- and hospital-acquired COVID-19 in future studies on COVID-19 may allow for more accurate interpretation of results. Highlights: COVID-19 depicts a wide spectrum of disease severity. Poor prognosis is associated with increasing age and co-morbidities. Community and hospital COVID-19 represent two separate sub-entities of the disease. This study shows significant differences observed between the two cohorts.